Pengembangan Media Pembelajaran Scrapbook Berbasis Canva Pada Tema 8 Subtema 1 Untuk Siswa Kelas V Sd Negeri 16 Urat Timur T.A 2022/2023 - Rotua Situmorang; Erlinda Simanungkalit; Demmu Karo-karo; Eva Betty Simanjuntak; Lidia Simanuhuruk (CENDEKIA: Jurnal Ilmu Sosial, Bahasa dan Pendidikan, 2023)
This study focuses on analyzing the validity of developing learning media, knowing the practicality and effectiveness of developing Canva-based scrapbook learning media on the theme 8 sub-themes 1 learning 4 class V SD Negeri 16 Urat Timur T.A 2022/2023. The problem in this study is that the learning media used in the learning process are still conventional media, the lack of use of learning media that utilizes technology, students find it difficult to understand learning material, and learning is still teacher- centered so that students are less active in the learning process. This research is a development research (Research and Development) using the ADDIE development model (Analysis, Design, Development, Implementation, Evaluation). The subjects of this study were fifth grade students and the object of this research was Canva-based scrapbook learning media. The results of material validation by material experts obtained a percentage of 85% in the "Very Eligible" category and media validation by media experts obtained a percentage of 94% in the "Very Eligible" category. The practicality test by educational practitioners obtained a percentage of 98% in the "Very Practical" category. The results of the media effectiveness test through the pretest obtained an average of 53.3 with a completeness percentage of 22.2% in the "Not Effective" category while in the posttest obtained an average of 85.5 with a 100% completeness percentage in the "Very Effective" category. So it can be concluded that the developed Canva-based scrapbook learning media is feasible, practical, and effective for use in learning activities in elementary schools.